THE URGENCY OF COLLATERAL IMPLEMENTATION IN THE MUDHARABAH FINANCE OF SHARIA BANKING IN INDONESIA - Fauzi, Wetria; Wulandari, Ratih Agustin; Efendi, Raimon (LPPM STIH Putri Maharaja, 2023)
Mudharabah financing is a transaction based on the principle of cooperation, so it does not require collateral. But financing does not always run smoothly. Finally, Islamic banks require collateral in mudharabah financing. Of course, it is a debate among scholars. For this reason, the purpose of this study is to identify the basis for applying collateral to mudharabah financing, and setting collateral binding for mudharabah financing in Islamic banking. The research objectives will be answered by empirical normative legal research methods which analyze the norms and provisions that apply, supported by field research in the form of interviews, and observation as reinforcement. The identification carried out resulted in First, the ijtihad method is the basis for the obligation to provide collateral in mudharabah financing by not overturning the original concept with the Istihsan method, and adhering to the provisions in UUPS, PBI Number: 7/46/PBI/2005 concerning Contracts for Collection and Distribution of Funds for Banks conducting business activities based on Sharia Principles, and DSN Fatwa Number: 07/DSNMUI/IV/2000 concerning Mudharabah Financing (Qiradh). Second, Islamic banking has not regulated the binding of collateral to mudharabah financing in Islamic banking, so in practice Islamic banking uses guarantee institutions that are used by conventional banks.